Partisipasi Perempuan pada Pemilihan Kepala Desa di Desa Kuala Sempang Kecamatan Seri Kuala Lobam Kabupaten Bintan - Desmayeti Arfa; M Miswanto (Jurnal Empirika, 2018)
Woman political participation means active involvement both individual or group in government process which has impact in life. Participation is more than a government method, it has a big goal, to unite society and to educate citizen about art of government. Democracy system has to maximize quantity and intencity of participation all society include woman, and also to expand social life which is apply the principle of democracy. The purpose of this study is to identify level of woman participation in election of village head at Kuala Sempang Village, Seri Kuala Lobam Subdistrict, Bintan Regency. This study uses qualitative approach by giving review and description about woman participation in election of village head at Kuala Sempang Village, Seri Kuala Lobam Subdistrict, Bintan Regency. The amount of population is 1,143 people, and sample is taken by accidental technique, the informant who is meet by accident while the election go on. The result of this study is level of woman participation in election of village head at Kuala Sempang Village, Seri Kuala Lobam Subdistrict, Bintan Regency is very highly. It can be looked from the increase of woman participation in the election, although most of them said that all of this participation is to support village head candidate which is trusted as public figure, such as head of neighborhood association, head of administrative unit at the next-to-lowest level in city, moreover the candidate is a person who was supported by member of Indonesian Legislative Assembly although he/ she does not have any position. In other word, the reason why woman participation is so highly because there are movement to support local elite politic.